UBE2D3 Activates SHP-2 Ubiquitination to Promote Glycolysis and Proliferation of Glioma via Regulating STAT3 Signaling Pathway - Pan, Zhenjiang; Bao, Jing; Zhang, Liujun; Wei, Shepeng (Frontiers in Oncology, 2021)
Glioma is a primary brain cancer with high malignancy and morbidity. Current management for glioma cannot reach optimal remission. Therefore, it is necessary to find novel targets for glioma treatment. Ubiquitin-conjugating enzyme E2 D3 (UBE2D3) is involved in the pathogenesis of various kinds of cancer. However, its role in glioma remains unclear. Our study aims to explore the function and underlying mechanism of UBE2D3 in the development of glioma. By analysis with The Cancer Genome Atlas-Glioblastoma multiforme (TCGA-GBM) dataset, we found that UBE2D3 was highly expressed in glioma and it is positive correlation with glycolysis, apoptosis, and STAT3 pathway. Then, we explore the effects of UBE2D3 knockdown in the biological functions of glioma cell lines. Cell proliferation and apoptosis were estimated by cell counting kit-8 assay and flow cytometry. Extracellular acidification rate and oxygen consumption rate were estimated to determine the level of cell glycolysis. Xenograft experiments were performed to identify in vivo function of UBE2D3. The results showed that the inhibition of UBE2D3 could suppress the proliferation, glycolysis, and STAT3 phosphorylation of GBM both in vitro and in vivo. UBE2D3 could interact with SHP-2 and promoted its ubiquitination, which elevated the activation of STAT3 pathway. Overexpressed SHP-2 could reverse the effect of UBE2D3 and they shared contrary expression patterns in glioma and normal brain tissues. In summary, our study revealed that UBE2D3 could promote the ubiquitination of SHP-2, which activated STAT3 pathway and promoted glioma proliferation as well as glycolysis. UBE2D3 could be a potential target for glioma treatment.